Characterization of field‐scale spray drift deposition and non‐target plant biological sensitivity: a corn herbicide (mesotrione/s‐metolochlor) case study. Issue 7 (18th May 2022) - Perkins, Daniel B.; Abi‐Akar, Farah; Goodwin, Gregory; Brain, Richard A.
Abstract: BACKGROUND: This work reports a combined, field‐scale spray drift deposition and plant bioassay study for a pre‐mixture of the herbicides mesotrione and s‐metolachlor. Wind direction data and field dimensions were used to evaluate the potential for spray drift to bypass downwind sampling devices. Variability in resulting spray drift across downwind distances was assessed alongside wind speed measured at on‐site weather stations. Measured wind angles were used to geometrically adjust traveled drift particle distances and enabling isolation of wind direction impact from wind speed. Further, the use of single and multiple in‐field monitoring locations was compared to quantify the benefit of higher‐resolution meteorological sampling. RESULTS: Generally, increased wind speed resulted in significantly greater herbicide deposition at distances proximal to the edge of the spray zone. According to the drift deposition curves that included wind speed data from single and multiple onsite weather stations, trials with relatively higher wind speeds were associated with greater spray drift deposition at relatively close sampling distances downwind from the application area. Only marginal improvement of linear mixed‐effects model fit was observed when including data from three weather stations, compared to the fit from a single weather station or absence of weather data in the model. Using tomato and lettuce plant bioassay species, the overall no‐effect distance was 3.0 m (10 ft). CONCLUSION: Results from this study are informative to refine pesticide risk assessment for non‐target plants and indicate that a single weather station is sufficient to capture potential influential effects from wind speed and direction on spray drift. © 2022 Society of Chemical Industry. Abstract : One of three tripod‐mounted anemometers used to collect real‐time, high‐resolution wind speed and direction during each spray drift trial. These data were used in a linear mixed‐effects statistical model to characterize the role of meteorological conditions related to physical spray drift. © 2022 Society of Chemical Industry.